Biogeomorphic impact of oligochaetes (Annelida) on sediment properties and Salicornia spp. seedling establishment - M. vanRegteren; R. tenBoer; E. H. Meesters; A. V. deGroot (Ecosphere, 2017)
Abstract Oligochaetes (Annelida) are active bioturbators that can be present in high densities in the transition zone between intertidal flats and salt marshes, though their occurrence and functional role remain understudied. This study aimed to clarify the biogeomorphic role of oligochaete bioturbation in facilitating or hindering vegetation establishment. Two microcosm experiments were performed to assess the effect of oligochaete bioturbation on sediment properties, oxidation depth, algal biomass, seed distribution, and germination success of pioneer species Salicornia spp. Oligochaetes created burrow networks in the sediment matrix, which, together with upward conveyor belt feeding, lead to substrate mixing. Sediment reworking rates of oligochaetes were compared with those of polychaete macrofauna. Bioturbation and bio‐irrigation of burrows can stimulate resource flows into the sediment. Oxidation depth increased almost tenfold in the presence of oligochaetes. Their bioturbation did not seem to affect sediment properties such as dry bulk density, porosity, and organic matter content. Sediment reworking, however, significantly reduced algal biomass at the surface with possible cascading effects on sediment stability and erodibility. Oligochaete conveyor belt feeding buried Salicornia spp. seeds until below the critical germination depth, thus negatively affecting Salicornia spp. germination and seedling establishment. Our study indicates that small, though numerous, oligochaete bioturbators may reduce lateral expansion potential of salt marshes by hindering the establishment of pioneer vegetation in the transition zone. Additionally, in dynamic fine‐grained habitats, these oligochaetes have the feature to quickly oxygenate the sediment top layer.